Effect of the pelletized sludge biochar on inhibiting sulfamethoxazole transport in mariculture sediments - Liang Weidong; Ren Guoliang (E3S Web of Conferences)
The misuse of antibiotics in intensive mariculture has turned sediments into antibiotic reservoirs, and their transport has exacerbated the spread of drug-resistant bacteria, threatening coastal ecological security and human health. Current remediation using powdered biochar is constrained in engineering applications due to issues including easy loss and difficult recovery. To address antibiotic transport (e.g., sulfamethoxazole, SMX) in mariculture sediments, we developed engineerable pelletized sludge biochar (SSPBC) through crosslinking chitosan with sludge biochar (SBC) prepared at gradient pyrolysis temperatures (300 °C, 500 °C, 700 °C). The SMX retention capacity of SSPBC was demonstrated in column transport experiments and validated in an actual aquaculture sediment system in Xincun Bay, Hainan. Results showed pyrolysis temperature critically affected SSPBC performance: When increasing pyrolysis temperature from 300 °C to 700 °C, SMX transport decreased from 98.86% to 76.71%; in the real sediment system, SSPBC-700 still maintained an excellent performance with a SMX mobility of 88.69%. Pelleting significantly improved the engineering applicability of biochar, and the pyrolysis temperature was positively correlated with pollutant retention efficiency. Notably, SSPBC-700 maintained high antibiotic retention performance in real media, establishing a feasible strategy for antibiotic contamination control in mariculture sediments.